Defensive froth in Arctiidae species (Lepidoptera) in the Rio Grande Sul State, Brazil - Molina, Tiziane Fernandes; Di Mare, Rocco (EntomoBrasilis, 2017)
Abstract. All the organisms are chemosensitive, besides being a source of substances capable of being perceived by other organisms. It is observed in Lepidoptera a great quantity of volatiles with signaling potential, or pheromones, which influence diverse behavioral aspects, such as reproduction, feeding and defense. In the Arctiidae family, the release of froth is a common defensive characteristic of these animals. This froth has not yet been investigated in regards to its pharmacological relationships, such as the relationship with secondary substances produced from host plants. This communication is intended to register the occurrence of this behavior of Phaloe cruenta (Hubner) and Hypercompe indecisa (Walker) recorded respectively in the Turvo State Park and in Alegrete, in the Rio Grande do Sul State. Espuma defensiva em espécies de Arctiidae no Rio Grande do Sul, Brasil Resumo. Todos os organismos são quimiossenssíveis, além de serem fonte de substâncias capazes de serem percebidas por outros organismos. Em Lepidoptera pode ser observada uma grande quantidade de voláteis com potencial sinalizador, ou feromônios, que influenciam diversos aspectos comportamentais, como na reprodução, alimentação e defesa. Na família Arctiidae, a liberação de uma espuma é característica comum e defensiva desses insetos. Tal espuma ainda não foi investigada quanto à sua relação farmacológica, como a relação com substâncias secundárias produzidas a partir de plantas-hospedeiras. Nesta nota pretende-se registrar a ocorrência desse comportamento de Phaloe cruenta (Hubner) e Hypercompe indecisa (Walker) registradas, respectivamente, no Parque Estadual do Turvo e em Alegrete, no Rio Grande do Sul.